Potret Relasi Suami-Istri Jamaah Mentaok Kotagede dalam Kajian Social Exchange - Ni'ami, Mohammad Fauzan (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2021)
This article aims to explore the portrait of the husband-wife relationship of the Yogyakarta Mentaok Congregation. The discussion is preceded by a study of husband and wife in the family, followed by a picture of the relationship pattern of the Mentaok Congregation Kotagede Yogyakarta, and then the shift in roles in the family of the Mentaok congregation in a social exchange review. The method used in this article is field research which is then analyzed deductively using a social exchange approach. The results of this study illustrate at least three patterns of relations between the Mentaok congregation: first, husband and wife work, and the wife takes care of domestic work. Second, the husband and wife work while other people care for their household work. The third form is husband and wife work, and both plunge into the domestic sphere. In a review of social exchange, researchers found that there is reciprocity in the family of the Yogyakarta Kotagege Mentaok Congregation, which is mutually beneficial and, at the same time, demands a sacrifice for a family. [Artikel ini bertujuan mengupas potret relasi suami-istri Jamaah Mentaok Yogyakarta. Pembahasan didahului dengan kajian suami istri dalam keluarga, dilanjut dengan potret pola relasi Jamaah Mentaok Kotagede Yogyakarta, dan kemudian pergeseran peran dalam keluarga jamaah mentaok dalam tinjauan social exchange. Metode yang dipakai dalam artikel ini adalah field research yang kemudian dianalisis secara deduktif dengan menggunakan pendekatan social exchange. Hasil penelitian ini menggambarkan setidaknya terdapat tiga pola relasi jamaah Mentaok, yaitu: pertama, suami dan istri bekerja serta istri mengurus pekerjaan domestik. Kedua, suami dan istri bekerja sedangkan orang lain yang mengurus pekerjaan domestiknya. Bentuk ketiga adalah suami dan istri bekerja dan keduanya terjun ke dalam wilayah domestik. Dalam tinjauan social exchange, peneliti mendapati adanya resiprositas dalam keluarga Jamaah Mentaok Kotagege Yogyakarta yang saling menguntungkan sekaligus menuntut adanya suatu pengorbanan pada suatu keluarga.]